Structure of type II collagen from sturgeon cartilage and its effect on adjuvant-induced rheumatoid arthritis in rats. Issue 11 (18th May 2022) - Li, Zhaoxia; Bai, Xue; Fan, Yan; Jia, Qiannan; Zhang, Hongwei; Hou, Hu
Abstract : SC-CII showed a triple-helix structure and alleviating effects on RA through the TLR4/MyD88-NFκB pathway. Abstract : The purpose of this paper was to extract and characterize type II collagen of sturgeon cartilage (SC-CII), and to explore the effects of taking SC-CII orally on rheumatoid arthritis (RA) in rats. SC-CII showed a triple-helix structure (RPN = 0.12), with d 1 of 11.82 Å and d 2 of 4.08 Å, which was analyzed by FT-IR, CD, XRD, and MS. It was constructed of the repeating tripeptide unit Gly–X–Y, where X and Y are generally Pro or Hyp, proved by amino acid composition and peptide mass fingerprinting. Furthermore, the effects of SC-CII on RA were evaluated. Ankle thickness was significantly decreased in SC-CII groups, with changes in lymphocyte proliferation also observed. Compared with the model control group, there was an evident decrease in TNF-α, IL-1β, COX-2, MCP-1, and TLR-4 mRNA levels, but no remarkable differences in APF, MMP-3, and MyD88 mRNA levels in the SC-CII groups. In addition, TNF-α, IL-1β, RF, Anti-CII Ab were significantly reduced in the SC-CII groups, proved by ELISA. Therefore, SC-CII showed alleviating effects on RA through the TLR4/MyD88-NFκB pathway.